A STUDY ON POPULATION DYNAMICS OF GELAM (MELALEUCA CAJUPUTI POWELL) AT TELUK GELAM SWAMP FOREST IN SOUTH SUMATRA AND ITS RELATIONSHIP WITH FIRE - Jaya Santri, Didi
Abstract The population dynamics of gelam / cajeput (Melaleuca cajuputi Powell) at two different locations in Teluk Gelam Swamp Forest South Sumatra and its relationship with fire was studied from December 1997 to June 1998. Southern side of the swamp forest was burned on December 1997, while the northern side was unburned. The two locations were separated in 0,5 km by a floodplain lake. Population with diameter on breast height (dbh) > 1 cm was counted in ten dbh size-class categories, that classified in threc life stages namely, sapling (1-10 cm dbh), pole (10-30 cm dbh) and tree (>30 cm dbh). The younger plant was classified in two categories, 0 - 30 cm and 30 - 150 cm height seedlings. The results showed that population of M. cajuputi had different size-class categories in two side of the swamp. In the northern side the gelam population had 1 - 50 cm dbh range, while in southern was 1 - 30 dbh range, both had modus 3-4 cm. The occurrence of small stem diameter (lesser than 3 cm dbh) of M. cajuputi indicated disturbance such as fire, and also due to intraspesific competition on light. The population structure of M. cajuputi was influenced by swamp forest fire that destroyed the young trees up to 3-cm dbh, while the older regrowth vegetatively. On the other hand, fire play as a trigger factor for seed germination and increasing total number of the 0 - 30 cm seedlings up to 1000 % and 400 % for 30 - 150 cm seedlings. The total number of younger seedlings had a positive relation to the increasing of light intensity and negative relation to the canopy cover, while the older ones were not show good correlation to the both factor. (p < 0,01).